2014
DOI: 10.1186/1471-2369-15-41
|View full text |Cite
|
Sign up to set email alerts
|

A novel SMARCAL1 mutation associated with a mild phenotype of Schimke immuno-osseous dysplasia (SIOD)

Abstract: BackgroundSchimke immuno-osseous dysplasia (SIOD, OMIM #242900) is an autosomal-recessive pleiotropic disorder characterized by spondyloepiphyseal dysplasia, renal dysfunction and T-cell immunodeficiency. SIOD is caused by mutations in the gene SMARCAL1.Case presentationWe report the clinical and genetic diagnosis of a 5-years old girl with SIOD, referred to our Center because of nephrotic-range proteinuria occasionally detected during the follow-up for congenital hypothyroidism. Mutational analysis of SMARCAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…PTX-3 serum levels were tested on serum samples drawn at the time of nephrectomy in the whole study population. Circulating PTX3 was measured was assayed using a commercially available ELISA Kit, according to the manufacturer's instructions (R&D Systems, Minneapolis, MN), as previously described [66,67].…”
Section: Ptx-3 Serum Level Assessmentmentioning
confidence: 99%
“…PTX-3 serum levels were tested on serum samples drawn at the time of nephrectomy in the whole study population. Circulating PTX3 was measured was assayed using a commercially available ELISA Kit, according to the manufacturer's instructions (R&D Systems, Minneapolis, MN), as previously described [66,67].…”
Section: Ptx-3 Serum Level Assessmentmentioning
confidence: 99%
“…7 Mutations in SMARCAL1 are linked to Schimke immuno-osseous dysplasia (SIOD), an autosomal recessive disorder characterized by pleiotropic phenotypes. [8][9][10][11][12] In this review, we will expand on the biophysical and functional characteristics of SMARCAL1.…”
Section: Introductionmentioning
confidence: 99%
“…In more severe cases of nephrotic syndrome and/or end-stage chronic renal failure stage, renal transplantation is indicated and there are no reports of post-transplant nephrotic syndrome, although infectious and cerebrovascular complications can still occur, since the SMARCAL mutation affects many systems beyond glomeruli. 2 There is no consensus as to bone marrow transplantation as treatment for marrow involvement. 12 It has been reported that patients with SIOD generally die within the first two decades of life by: infections (23%), stroke (17%), renal failure (15%), pulmonary hypertension and congestive heart failure (15%), organ transplant complications (9%), complications of lymphoproliferative diseases (9%), gastrointestinal hemorrhage (6%), bone marrow aplasia (3%) and acute restrictive lung disease (3%).…”
Section: Discussionmentioning
confidence: 99%
“…2 The only known cause is the mutation in the SMARCAL 1 gene, HepA-related protein; however, approximately 50% of patients do not have this mutation. SMARCAL 1 is a fundamental remodeling protein for genome integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation